Repurposing Cyanine NIR‐I Dyes Accelerates Clinical Translation of Near‐Infrared‐II (NIR‐II) Bioimaging. Issue 34 (9th July 2018) - Zhu, Shoujun; Hu, Zhubin; Tian, Rui; Yung, Bryant C.; Yang, Qinglai; Zhao, Su; Kiesewetter, Dale O.; Niu, Gang; Sun, Haitao; Antaris, Alexander L.; Chen, Xiaoyuan
Abstract: The significantly reduced tissue autofluorescence and scattering in the NIR‐II region (1000–1700 nm) opens many exciting avenues for detailed investigation of biological processes in vivo. However, the existing NIR‐II fluorescent agents, including many molecular dyes and inorganic nanomaterials, are primarily focused on complicated synthesis routes and unknown immunogenic responses with limited potential for clinical translation. Herein, the >1000 nm tail emission of conventional biocompatible NIR cyanine dyes with emission peaks at 700–900 nm is systematically investigated, and a type of bright dye for NIR‐II imaging with high potential for accelerating clinical translation is identified. The asymmetry of the π domain in the S1 state of NIR cyanine dyes is proven to result in a twisted intramolecular charge‐transfer process and NIR‐II emission, establishing a general rule to guide future NIR‐I/II fluorophore synthesis. The screened NIR dyes are identified to possess a bright emission tail in the NIR‐II region along with high quantum yield, high molar‐extinction coefficient, rapid fecal excretion, and functional groups amenable for bioconjugation. As a result, NIR cyanine dyes can be used for NIR‐II imaging to afford superior contrast and real‐time imaging of several biological models, facilitating the translation of NIR‐II bioimaging to clinical theranostic applications. Abstract : Significantly reduced photon scattering and tissue autofluorescence in the NIR‐II window facilitate higher‐resolution bioimaging compared to the traditional NIR‐I one. However, the existing NIR‐II agents face significant technical and regulatory hurdles prior to clinical translation. Fortunately, spectroscopic characterization of clinically/commercially available near‐infrared dyes identifies the bright emission tail in the 1000–1300 nm range, accelerating clinical translation of NIR‐II imaging.